2011
DOI: 10.5713/ajas.2011.r.06
|View full text |Cite
|
Sign up to set email alerts
|

Meta Analysis to Draw the Appropriate Regimen of Enzyme and Probiotic Supplementation to Pigs and Chicken Diets

Abstract: Along with the recent changes in animal feed supply circumstances, many enzyme and probiotic feed supplements have been introduced and applied to pigs and chicken diets. Therefore, both selection of the appropriate feed supplements and their proper supplementation becomes critical to justify the supplementation. Meta-analysis was proposed as an appropriate tool to assess the large amount of relevant information. In this review, reliable data from recent publications was compounded then analyzed to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Today, addition of probiotic in diet is a common strategy for animal nutrition, because probiotic is a natural growth promoter instead of feed antibiotic (Rekiel et al 2007). Adding probiotic in the diet improves the animal immune system and the host's resistance to enteric pathogens, affects intestinal morphology as well as intestinal function, feed conversion, weight gain and performance of birds (Dalloul et al 2003, Chichlowski et al 2007, Vila et al 2009, Ohh 2011. Li et al (2006) also reported that addition of Bacillus subtilis culture to the layer diet decreased cholesterol concentration in egg yolk.…”
Section: Introductionmentioning
confidence: 99%
“…Today, addition of probiotic in diet is a common strategy for animal nutrition, because probiotic is a natural growth promoter instead of feed antibiotic (Rekiel et al 2007). Adding probiotic in the diet improves the animal immune system and the host's resistance to enteric pathogens, affects intestinal morphology as well as intestinal function, feed conversion, weight gain and performance of birds (Dalloul et al 2003, Chichlowski et al 2007, Vila et al 2009, Ohh 2011. Li et al (2006) also reported that addition of Bacillus subtilis culture to the layer diet decreased cholesterol concentration in egg yolk.…”
Section: Introductionmentioning
confidence: 99%
“…The prebiotic nature of MOS has been demonstrated previously and has also been revealed to have a positive effect on gut motility [21,32]. Although there were few reports on oligosaccharide production from KGM [33] and CM, and copra mannan hydrolysates were used for prebiotic analysis, resulting in 0.09-2.15 log cfu/mL enhancing activity [34], but no report was available with LBG, GG, WB, and OB.…”
Section: Evaluation Of Mos For Use As a C-source By Bacteriamentioning
confidence: 94%
“…5). The results in the been reported to reduce incidence of pathogens in animals [8,32]. Yet, few studies have investigated MOS as prebiotic to check their inhibitory effect.…”
Section: Evaluation Of Mos For Use As a C-source By Bacteriamentioning
confidence: 99%
“…The efficacy of PTC was affected by the age of the broilers. Since the young broiler gastrointestinal tract is unable to secrete sufficient amounts of pepsin and gastric acid, this could explain why phytase was more efficient with more mature broilers (Ohh, 2011). It is concluded that partly replacing non-genetically modified corn with PTC can fully keep good growth performance despite halving the amount of diacalcium phosphate in the diet.…”
Section: Growth Performancementioning
confidence: 99%